Physical and Chemical Components of Cuba's Rain: Effects on Air Quality. (12th August 2014) - Préndez, Margarita; López, Rosemary; Carrillo, Ernesto
Abstract : The objective of this study was to analyze the influence of the physical and chemical components of rain affecting air quality in Cuba. Samples were obtained from pollution monitoring stations throughout Cuba. Different chemical analyses including elements and ions were conducted. Meteorological data was also included for the analysis. Results show that the pH was slightly basic for most stations, except those of the eastern region which exhibit pH values below 5.6. The major anthropogenic sources of ions are the burning of fossil fuel by power plants, cement factories, and nickel-processing industries and the burning of biomass through poor agricultural practices. The western region exhibited increased concentrations ofN O 3 - andS O 4 2 - during the dry season, most likely due to the long-range transport of pollutants from the northeastern United States as well as local pollutants. Marine aerosols clearly influence Cuba's rain. Only a small fraction of the potentially acidic ions contributes to the free acidity of Cuba's rainwater, mainly due to the neutralizing capacity of some ions such as Cl -, Na +, Ca +2, andN H 4 + . The implementation of abatement techniques for SO2 and NOX and some elements emissions from major stationary sources will be an effective measure to improve air quality in Cuba.